World Economic Outlook, October 1999 : Safeguarding Macroeconomci Stability at Low Inflation. (World Economic Outlook; World Economic Outlook, 1999)
Supporting Studies for the World Economic Outlook, prepared by IMF staff, provide a more detailed analysis of issues recently covered in the main pubication. The current edition includes studies of globalization and growth, the future of the international financial system, currency crises, business cycles and exchange rates, supply-side issues in the contractions experienced in the Baltics, Russia, and other countries of the former Soviet Union, and challenges to European labor markets posed by European Economic and Monetary Union (EMU).